(NhOLODNYJ DOM(B: [(NrOMAN(B];s (NgLAWY (BXXXI-LXVII /s (N~ASTX (B18s - (NdIKKENS(B, (N~ARLXZs ((NmOSKWA(B:s (NgOSUDARSTWENNOE IZDATELXSTWO HUDOVESTWENNOJ LITERATURY(B,s, 1960)
(Nw (B18 (NTOM sOBRANIQ SO^INENIJ WO[LO PRODOLVENIE ROMANA (B"(NhOLODNYJ DOM(B". (NgLAWY (BXXXI-LXVII.s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NrOMANs